A generalised diffusion-based file replication scheme for load balancing in P2P file-sharing networks. (17th January 2013) - Takaoka, Masanori; Uchida, Masato; Ohnishi, Kei; Oie, Yuji
We propose a generalised diffusion-based file replication scheme for load balancing in unstructured P2P file-sharing networks. The generalised method is derived by replacing the replication probability of a peer used in our previous study with a new expression. In the previous expression, the replication probability is defined to be proportional to the difference between its own load and the average load of its neighbour peers. We show here that the replication probability can instead be expressed as a simple average of one defined to be negatively proportional to its own load and one defined to be proportional to the average load of its neighbour peers. The generalised method (a) includes the above three methods as special cases, (b) can control the trade-off between search and load balancing performances, (c) has a physical analogy to diffusion phenomena, and (d) achieves a good balance in the trade-off differently from our previous method.